Japan in the Islamic sources: "problematic significance and determine the place of the " Wak Wak - Fawzi Jasim, Nibras (Al-Adab Journal, 2019)
The paper deals with one of the problems that are summarized by the sources of the Islamic heritage, which require reconsideration and recitations of the historical texts in order to settle their contents. The problem of this paper is based on the location of the Wak Wak, which remained vague and ambiguous even after being subjected to research and investigation of historians and scholars. Therefore, this does not prevent researching this problematic issue according to the logic of historical treatment as long as previous researches did not provide a decisive opinion in this regard. Depending on some data tried to examine the weight of one of the hypotheses that go to these islands is a description of what is now called Japan.